2006
DOI: 10.1016/j.amjhyper.2005.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Blood Pressure Monitoring and Risk of Cardiovascular Disease: A Population Based Study

Abstract: Ambulatory BP provided prognostic information about cardiovascular disease better than office BP. Isolated office hypertension was not a risk factor and isolated ambulatory hypertension tended to be associated with increased risk. A blunted BP decrease at night was a risk factor in subjects with daytime ambulatory hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
249
4
13

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(277 citation statements)
references
References 29 publications
11
249
4
13
Order By: Relevance
“…[13][14] Extensive studies have clearly demonstrated predictive information of cardiovascular outcomes in population-based surveys. [15][16][17][18][19] In addition to the mean 24-h BP, nocturnal BP has frequently been considered an important predictor of both target-organ damage and cardiovascular events. [18][19][20] A normal dipping pattern (dipper) is seen when the drop in the average SBP during the night is 410% of the mean daytime SBP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14] Extensive studies have clearly demonstrated predictive information of cardiovascular outcomes in population-based surveys. [15][16][17][18][19] In addition to the mean 24-h BP, nocturnal BP has frequently been considered an important predictor of both target-organ damage and cardiovascular events. [18][19][20] A normal dipping pattern (dipper) is seen when the drop in the average SBP during the night is 410% of the mean daytime SBP.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19] In addition to the mean 24-h BP, nocturnal BP has frequently been considered an important predictor of both target-organ damage and cardiovascular events. [18][19][20] A normal dipping pattern (dipper) is seen when the drop in the average SBP during the night is 410% of the mean daytime SBP. Individuals with a non-dipper pattern (reduction in nighttime SBP o10%) are at increased risk for cerebrovascular and cardiovascular complications Nocturnal dipping and endothelial function in resistant hypertension T Quinaglia et al when compared with individuals with a normal dipper profile.…”
Section: Discussionmentioning
confidence: 99%
“…However, overall, the prognostic values of nondipping were inconsistent; the reasons may in part be explained by the arbitrary and varying definition of nondipping, poor reproducibility, differences in the study population or differences in the adjusted factors used in each study. 8,20,30 A systematic review by Hansen et al 20 revealed that nondipping was associated with higher total mortality and cardiovascular events in the general population, although it added only 0.1% prognostic value beyond that of the 24-hour BP levels.…”
Section: Nocturnal Bp Dipping and Cardiovascular Riskmentioning
confidence: 99%
“…3 Accordingly, ambulatory blood pressure measurement is a better predictor of cardiovascular morbidity and mortality than office blood pressure. [8][9][10][11][12][13][14][15] Randomized studies using ambulatory blood pressure measurement for the management of antihypertensive treatment are scarce. 16 In one study, less intensive antihypertensive drug treatment was observed with the use of 24-h blood pressure measurement, whereas overall blood pressure con-trol was maintained in both treatment groups.…”
Section: Introductionmentioning
confidence: 99%
“…This would be highly desirable because of the high cardiovascular risk in these individuals. 12,17,18 We therefore designed the present study to compare 24-h ambulatory blood pressure to standard office blood pressure in the management of antihypertensive therapy in individuals with sustained hypertension.…”
Section: Introductionmentioning
confidence: 99%